Kansas State University swine enterprise record summary - Richert, B.T.; Langemeier, Michael R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Approximately 15 swine operations are enrolled in the 1993 to 1994 Kansas Swine Enterprise Record Program provided by Kansas State University. This program evaluates biological and economic performance and is part of a cooperative record-keeping project with extension personnel and swine producers in Kansas, Nebraska, and South Dakota. Records are summarized every 6 months, and the corresponding data are pooled to form state and regional averages. This summary includes the combined data for the 38 farrow-to-finish operations in the three-state region. The semi-annual data represent the first 6 months of 1994, whereas the annual data are for the 12-month period of July 1, 1993 to June 30, 1994. Profit per cwt of pork produced for these 38 producers averaged a loss of $0.85 for the first 6 months of 1994 and a loss of $2.92 for the past year. Profits varied substantially between producers. Producers in the top one-third in terms of profitability had average profits of $4.47 per cwt, whereas producers in the bottom one-third had average losses of $10.05 per cwt for the year. Critical factors separating low-and high-profit producers included feed costs, unpaid labor, fixed costs, and death loss.
Typo of author's name M. L. Langemeier; should be M. R. Langemeier.
Keywords: Swine; Enterprise; Records; Analysis; Profitability